O protagonismo juvenil na transformação social: análise de redações do vestibular, correlacionada ao questionário socioeconômico dos vestibulandos, através de descoberta de conhecimento em bases de dados - Freitas dos Santos, Gerardo Magela (2010)
Faced with the huge data collection underutilized in educational management, this dissertation studied the perception of school students about youth participation in social transformation through examination of the college entrance essays, a Salesian Institution of Higher Education, correlated to socioeconomic questionnaire by Discovery knowledge Databases. The theoretical framework began with the study of youth participation, in the Salesian approach; considered Lacan's contribution, on the real, the symbolic and the imaginary, and the approach of Maturana and Varela, seeing humans as autopoietic organisms, living in structural coupling, natural, social, cultural and linguistic; finally, to understand youth involvement, as a provision for action, estudouse proactivity of the social agent in relation to the social environment and in relation to himself, based on the concept of habitus Bourdieusian.